Răspuns :
a) x+2=15
x=15-2
x=13
b) x-11=4
x=4+11
x=15
c) x+9=21
x=21-9
x= 12
d) 15=x-34
x=34-15
x=19
e) 49=x+27
x=27+49
x=76
f) x=20+61
x=81
x=15-2
x=13
b) x-11=4
x=4+11
x=15
c) x+9=21
x=21-9
x= 12
d) 15=x-34
x=34-15
x=19
e) 49=x+27
x=27+49
x=76
f) x=20+61
x=81
a)
X+2=15
X=15-2
X=13
b)
X-11=4
X=4+11
X=15
c)
X+9=21
X=21-9
X=12
d)
15=X-34
X=15+34
X=49
e)
49=X+27
X=49-27
X=22
f)
61=X-20
X=61+20
X=81
X+2=15
X=15-2
X=13
b)
X-11=4
X=4+11
X=15
c)
X+9=21
X=21-9
X=12
d)
15=X-34
X=15+34
X=49
e)
49=X+27
X=49-27
X=22
f)
61=X-20
X=61+20
X=81